An Interpretation of Reversed Flow Curve In Hec-RAS 2D Time Based Cross Section - Eko Widyanto, Bambang; Radhitya Akbar, Sandy; Hasan, Fuad (International Journal of Psychosocial Rehabilitation, 2020)
Modelling software is important nowadays, especially in a country which troubled with a flood. Flood can be happened from various cautions from the Dam failure, heavy rain, tidal and etc. HEC RAS is one of modelling software that often used by an engineer to create a flood model. It even can calculate an unsteady flow in 2D simulation and use a discharge calculation as an initial boundary data and use a Digital Elevation Model as flow areas. The modelling results is a flood plain area, a flow in cross section area, velocity and etc. Some of flow results that shown in graphic area is reversed and sometime make a miss interpretation. The reversed graphic is caused by negative value of Velocity which is a part of flow equation. Based the velocity equation the possible negative value is come from the Slope value which can be read negative by the system. To interpret it, we need to see how the long section is and change the value to positif.